Comparative study of the use of natural and artificial coagulants for the treatment of sullage (domestic wastewater). Issue 1 (1st January 2017) - Ugwu, S.N.; Umuokoro, A.F.; Echiegu, E.A.; Ugwuishiwu, B.O.; Enweremadu, C.C.
Abstract: This work presented a comparative study of the effectiveness of natural coagulant ( Moringa oleifera and hydrolyzed cassava) extracts and artificial coagulant (alum) as primary coagulants for sullage from homes and cafeteria at the University of Nigeria, Nsukka. Stock solutions of these coagulants were prepared, and jar test of their varying mixing ratios used to obtain optimum dosages of 200, 30 and 1, 000 mg/l for Moringa, alum and cassava respectively. The effects of these optimum dosages were tested against turbidity, pH, BOD, nutrients, hardness and coli form. All tested parameters were significantly sensitive to concentrations of used stock solutions. 100% Moringa seed extract resulted in all the treated parameters (except turbidity) being within tolerable limits. The stock solution of 100% Alum also showed all tested parameters (except pH) to be within the standards for drinking water. The combination of Moringa and alum stock solutions at 50% each (A50M50) showed the overall best result with the resultant water fit for drinking. The result of the comparative test showed that alum with its residual and health implications can be successfully replaced, partially or wholly, with natural coagulants.